2015
DOI: 10.3233/jad-142832
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Production in Response to Amyloid-β Differs between Slow and Fast Decliners in Patients with Alzheimer’s Disease

Abstract: Abstract. We investigated IL-10 and IL-6 production in amyloid-␤ (A␤) stimulated peripheral blood mononuclear cells (PBMCs) in twenty Alzheimer's disease (AD) patients with slow progression, eleven with fast progression, and twenty age-matched controls. Promoter polymorphisms in IL-10 (position −592, −819, −1082), IL-6 (−174), transforming growth factor-␤1 (TGF-␤1) (−10, −25), interferon-␥ (IFN-␥) (−874), and tumor necrosis factor-␣ (TNF-␣) (−308) genes were analyzed. IL-10 production after A␤ stimulation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
(65 reference statements)
1
16
0
1
Order By: Relevance
“…Importantly, serum IL-10 levels are affected in individuals with AD (Asselineau et al, 2015;Remarque et al, 2001;Swardfager et al, 2010). In peripheral blood mononuclear cells, IL-10 synthesis is almost ceased in fast cognitive decliners, whereas its level is slightly increased in slow cognitive decliners with AD (Asselineau et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, serum IL-10 levels are affected in individuals with AD (Asselineau et al, 2015;Remarque et al, 2001;Swardfager et al, 2010). In peripheral blood mononuclear cells, IL-10 synthesis is almost ceased in fast cognitive decliners, whereas its level is slightly increased in slow cognitive decliners with AD (Asselineau et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The association of interleukin-10 polymorphisms with risk of Alzheimer's disease was recently reported (79). It was also reported that IL-10 production in response to amyloid-␤ differs between AD patients with slow and fast progression of cognitive decline, based on the observation that A␤-stimulated peripheral blood mononuclear cells from slow decliners present higher IL-10 levels compared with controls, whereas in fast decliners, IL-10 production was abolished (80). These findings suggest that the increase in IL-10 levels found in MSC/neuronal cocultures may represent an important component of the neuroprotective action of MSCs, by neutralizing the cytotoxic inflammatory process induced by A␤Os and down-regulating the synthesis of pro-inflammatory cytokines, as proposed previously (81).…”
Section: Neuroprotective Potential Of Mscs In Alzheimer's Diseasementioning
confidence: 92%
“…It is primarily produced by T cells and natural killer cells but can also be secreted by microglia and astrocytes (Fultz et al, 1993). IFN-γ is upregulated in the AD brain (Huberman et al, 1994) and a polymorphism is associated with fast progressing AD, suggesting it could play a detrimental role in the course of AD (Asselineau et al, 2015).…”
Section: Il-1βmentioning
confidence: 99%